Correlation of microstructures with electrical and optical properties in zinc oxide ceramic semiconductor - Wan Ab Rahman, Wan Norailiana (2016)
Zinc oxide (ZnO) semiconductor is a polycrystalline ceramic exhibiting highly nonlinear (I-V) behavior. In polycrystalline ZnO materials, understanding and controlling the microstructure is very important since the electrical and optical band gap properties are directly influenced by the microstructure effect. The question about how the microstructural properties evolve with the electrical and optical properties in nanometer-to-micrometer grain-size region and what is the relationship of evolving microstructure properties with the physical properties of the ZnO has not been studied in depth. Hence, this research intend to explore the systematic study on parallel evolution from nanometere up to micrometer grain size between microstructure and material properties and the fundamental knowledge behind these parallel properties. Although there is numerous studies on the ZnO materials but the composition-microstructure relationship with the parallel evolution of the electrical and optical properties in nanometer-to-micrometer grain-size region have not yet been clarified. Doped-ZnO powders were milled using High Energy Ball Milling (HEBM) with different milling time. The doped-ZnO samples were sintered at two different ranges of sintering temperatures. The first range is from 500 until 1300 °C sintering temperatures with 100 °C increment for Batches A, C, D1, D2 and D3 samples. The second range is at lower sintering temperatures from 500 to 800 °C with 25 °C increment for Batch E samples. The phase purity of the samples were examined by XRD and the particle size distribution of the powder were observed using TEM. The surface morphology of the samples was examined using FESEM while the EDX measurement used to identify the elemental of the samples. The samples were characterized for the nonlinear coefficient (α) at room temperature using source measurement unit and for optical band gap energy, measurement was carried out by using UV-Visible spectrometer. Decreasing particle size would lead to improved grain growth control and homogeneity for better electrical and optical band gap characteristics. The α value increased as the grain size increased while the optical band gap decreased with increasing grain size. The HEBM technique has succesfully produced good electrical properties due to the well-formed microstructure even at low-sintering temperature and improved grain boundary characteristics. The nonlinear I-V characteristic of doped-ZnO sample is a grain-boundary phenomenon, and the electrical characteristics of the samples are directly related to the size of the ZnO grain. The highest value of α was found is 8 at 1100 °C sintering temperature for Co-doped sample while for Mn-doped sample the α value was found to be 7 at 1100 °C sintering temperature. The increment of α value with grain size was due to the larger potential barrier at the grain boundaries as the sintering temperature increased from 500 until 1100 °C. At 1200 and 1300 °C sintering temperature the α value decreased due to the decrement of potential barrier at the grain boundaries. The decrement was due to the diminished of Bi-rich phase at high sintering temperature. The HEBM technique also produced samples with smaller particle size, giving rise to a systematic decrease of band gap value associated with quantum confinement. The band gap value for Co-doped sample were vary from 3.2 to 2.5 eV at nanograin size below 1μm. Higher value of band gap at nanograin size contributes by this confinement and as the grain size increased, the variation of band gap value was decreased due to the growth of interface states at the grain boundaries.